ANALISIS SUPPLY CHAIN DAN VALUE CHAIN DI SUBAK PULAGAN BALI - Suasih, Ni Nyoman Reni; Wijaya, Putu Yudy (Buletin Studi Ekonomi, 2021)
Indonesia is one of the countries with the highest rice consumption in the world, and Bali is one of the provinces in Indonesia. Even so, the farmers were not yet prosperous and were only as price takers. The purpose of this study was to analyze the distribution channels of post-harvest rice in Bali Province through supply and value chain analysis. This study uses supply and value chain analysis, marketing efficiency analysis, and analyzes the relationship between farmers and intermediaries. Data was collected using snowball techniques, initiated by farmers in Subak Pulagan (an agricultural area designated as a world cultural heritage by UNESCO). The results showed that the post-harvest rice distribution system in Subak Pulagan consisted of three distribution channels. The best distribution channel is the third distribution channel, because farmers get the highest percentage of the retail price of rice, and the price received by consumers is also the lowest.